2009
DOI: 10.1074/jbc.m109.048884
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-5a-induced Phosphorylation of DARPP-32 Inhibits Breast Cancer Cell Migration in a CREB-dependent Manner

Abstract: Tumor cell migration plays a central role in the process of cancer metastasis. We recently identified dopamine and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32) as an antimigratory phosphoprotein in breast cancer cells. Here we link this effect of DARPP-32 to Wnt-5a signaling by demonstrating that recombinant Wnt-5a triggers cAMP elevation at the plasma membrane and Thr34-DARPP-32 phosphorylation in MCF-7 cells. In agreement, both protein kinase A (PKA) inhibitors and siRNAmediated knockdown of Frizzled-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 41 publications
(38 reference statements)
3
66
0
Order By: Relevance
“…One explanation is that a nonclassical NF-kB activity (p50-or p52-homodimer formation) induces IL-10 transcription together with certain transcription factors (e.g., cAMP-induced CREB activity) (39). Wnt5a induces cAMP and CREB activa- tion (40). We suggest that the mechanism behind Wnt5a-induced macrophage reprogramming is that Wnt5a acts as a feedback antagonist of TLR signaling with subsequent induction of antiinflammatory cytokines such as IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that a nonclassical NF-kB activity (p50-or p52-homodimer formation) induces IL-10 transcription together with certain transcription factors (e.g., cAMP-induced CREB activity) (39). Wnt5a induces cAMP and CREB activa- tion (40). We suggest that the mechanism behind Wnt5a-induced macrophage reprogramming is that Wnt5a acts as a feedback antagonist of TLR signaling with subsequent induction of antiinflammatory cytokines such as IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic contribution of heterotrimeric G proteins and downstream second messengers is still unclear, as discussed in section IX.A. However, second messengers, such as inositol phosphates, inositol pentakisphosphates (Gao and Wang, 2007), inositol 3-phosphates (Slusarski et al, 1997), phosphatidylinositol 4-trisphosphate (Qin et al, 2009), phosphatidylinositol 3,4,5-trisphosphate (Pan et al, 2008), calcium, or the cyclic nucleotides cGMP (Ahumada et al, 2002) and cAMP (Hansen et al, 2009), were reported to mediate WNT effects (see also Fig. 5).…”
Section: B Second Messenger Signalingmentioning
confidence: 99%
“…RAP is closely related to RHO-like proteins and, among other stimuli, is regulated by cAMP through a cAMP-binding GEF called exchange protein directly activated by cAMP (de Rooij et al, 1998). With the above-mentioned signaling axis through cAMP (Hansen et al, 2009) in mind, it seems likely that exchange protein directly activated by cAMP could mediate RAP activation. This connection however, is purely hypothetical and awaits experimental confirmation.…”
Section: G Wnt/rap Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, Chen and colleagues (6) first revealed PKA involvement in Wnt signaling. In 2008, Torii and colleagues (7) documented noncanonical Wnt/PKA signaling in dermal fibroblasts, and in 2009, Hansen and colleagues (8) demonstrated Wnt/cAMP/PKA signaling in breast cancer cells. Thus activation of this pathway by Wnts is not unique to osteoclast precursors, nor is it completely unexpected.…”
mentioning
confidence: 99%